2017
DOI: 10.1002/hbm.23845
|View full text |Cite
|
Sign up to set email alerts
|

Vicariously touching products through observing others' hand actions increases purchasing intention, and the effect of visual perspective in this process: An fMRI study

Abstract: The growth of online shopping increases consumers' dependence on vicarious sensory experiences, such as observing others touching products in commercials. However, empirical evidence on whether observing others' sensory experiences increases purchasing intention is still scarce. In the present study, participants observed others interacting with products in the first-or third-person perspective in video clips, and their neural responses were measured with functional magnetic resonance imaging (fMRI). We invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Consumers have become increasingly tolerant of purchasing products online, a medium not conducive to physical interaction with products prior to purchase. Research has shown that viewing touch increases purchase intention (Liu et al 2018) and that actual product touch is important when assessing and purchasing products (Grohmann, Spangenberg, and Sprott 2007;Holbrook 1983;McCabe and Nowlis 2003;Peck and Childers 2003). Yet when touch is translated to a digital environment and consumers view a hand interacting with a product, we wonder whether vicarious touch affects how consumers value products.…”
mentioning
confidence: 99%
“…Consumers have become increasingly tolerant of purchasing products online, a medium not conducive to physical interaction with products prior to purchase. Research has shown that viewing touch increases purchase intention (Liu et al 2018) and that actual product touch is important when assessing and purchasing products (Grohmann, Spangenberg, and Sprott 2007;Holbrook 1983;McCabe and Nowlis 2003;Peck and Childers 2003). Yet when touch is translated to a digital environment and consumers view a hand interacting with a product, we wonder whether vicarious touch affects how consumers value products.…”
mentioning
confidence: 99%
“…In contrast, retailers from web stores use vicarious‐touch strategies to induce consumers' virtual experience of touching a product. These vicarious‐touch strategies include, but are not limited to, inviting consumers to observe a human hand touching a product in a picture (Liu et al, 2018; Luangrath et al, 2022), imagine touching a product (Peck & Shu, 2009; Peck et al, 2013; Pino et al, 2020; Silva et al, 2021), view haptic cues contained in an online booking service (Lv et al, 2020; Silva et al, 2021) and place a haptic cue (i.e., a graspable object) besides the non‐graspable target product (Maille et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers recruited participants from different countries to study the effect of touching on product attitudes. These countries include, but are not limited to, China (e.g., Liu et al, 2018), Italy (e.g., Streicher & Estes, 2016), France (e.g., Racat et al, 2021), Canada (e.g., Grohmann et al, 2007), Brazil (e.g., Vieira, 2013), the United States (e.g., Peck & Wiggins, 2006), Israel (e.g., Ert et al, 2016), the UK (e.g., Marlow & Jansson‐Boyd, 2011), India (e.g., Jha et al, 2019), Austria (e.g., Hazeé et al, 2019), Australia (e.g., Heller et al, 2019) and New Zealand (e.g., Fenko et al, 2016). According to Hofstede (1993), people living in these countries differ from each other in one important cultural dimension: uncertainty avoidance.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Studies in cognitive psychology and consumer behavior have shown that observing hand haptic cues and product touch could stimulate vicarious touch experience. The process of automatically simulating others’ hand-touch actions appears psychologically and behaviorally ( Liu et al, 2018 ), even if the subjects rationally judge that the behavior does not come from themselves ( Wegner et al, 2004 ). This vicarious sensory experience also helps to infer its sensory characteristics and obtain sensory information about products ( Pino et al, 2020 ), thereby enhancing purchase and payment intention ( Luangrath et al, 2022 ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%